2019
DOI: 10.1111/bjd.17505
|View full text |Cite
|
Sign up to set email alerts
|

Genital psoriasis: the failure of dermatologists to identify genital involvement

Abstract: Linked Article: Larsabal et al. Br J Dermatol 2019; 180:647–656.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
0
9
0
2
Order By: Relevance
“…Although the prevalence of exclusive genital psoriasis is estimated at 2-5% of all patients with psoriasis, 31% of patients in the current sample reported lesions in the anal and/or genital areas. The prevalence of anogenital psoriasis reported in previous studies is probably underestimated, since a large portion of patients have reported they had not been examined previously for genital involvement [28,29]. The substantial proportion of patients with anogenital psoriasis in the present study resembles those found in the few previous studies on the epidemiology of psoriasis of the genital skin [5] and may be justified by the use of a patient-reported grid scheme to document the topology of psoriasis, which enabled the patients to disclose the involvement of anogenital areas regardless of whether they have previously discussed this sensitive topic with their physicians.…”
Section: Plos Onementioning
confidence: 89%
See 1 more Smart Citation
“…Although the prevalence of exclusive genital psoriasis is estimated at 2-5% of all patients with psoriasis, 31% of patients in the current sample reported lesions in the anal and/or genital areas. The prevalence of anogenital psoriasis reported in previous studies is probably underestimated, since a large portion of patients have reported they had not been examined previously for genital involvement [28,29]. The substantial proportion of patients with anogenital psoriasis in the present study resembles those found in the few previous studies on the epidemiology of psoriasis of the genital skin [5] and may be justified by the use of a patient-reported grid scheme to document the topology of psoriasis, which enabled the patients to disclose the involvement of anogenital areas regardless of whether they have previously discussed this sensitive topic with their physicians.…”
Section: Plos Onementioning
confidence: 89%
“…However, they presented better health and less QoL impairments in general than women, as assessed with the EQ VAS and DLQI. These results might be explained by the higher frequency of genital itching among females, which has been described as one of the most debilitating symptoms of genital psoriasis [ 28 , 29 , 31 ], and they also highlight the limitations of index measures to detect specific QoL impairments [ 32 ]. Worse perception of body image and higher prevalence of body dysmorphic concerns among females with skin diseases in general and with psoriasis in particular may also explain the gender differences in patient-reported health and QoL [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although genital psoriasis is a common manifestation of plaque psoriasis associated with reduced quality of life and sexual health (2,3,7), it is frequently overlooked in clinical practice (7)(8)(9), and there have been few clinical studies evaluating therapies for genital psoriasis (4,14,(16)(17)(18). Hence, well-established treatment options for genital psoriasis are limited and awareness among both healthcare providers and patients is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Genital psoriasis may present to multiple medical disciplines including primary care, dermatology, venereology, gynecology, urology, and sexual medicine (6). Despite the high prevalence and burden of genital psoriasis, approximately 46% of patients do not discuss their genital symptoms with their healthcare providers and only 40% of patients indicate having been examined for genital involvement (7)(8)(9). Thus, there is currently an unmet need for increased awareness of genital psoriasis among both patients and physicians to encourage appropriate diagnosis and treatment.…”
mentioning
confidence: 99%
“…However, generalized plaque or intertriginous psoriasis also affects the genital area in 29–40% of cases . In addition, the prevalence of anogenital psoriasis is likely to be underestimated because of reluctance of both patients and healthcare providers to discuss anogenital lesions and sexual quality of life (QoL) in routine care …”
Section: Introductionmentioning
confidence: 99%